Exploring Culinary Tourism and Female Consumer Preferences for Selected National Cuisines in Poland: A Sensory and Preference Analysis of Food Products from Four Countries - Agata Kiciak; Wiktoria Staśkiewicz-Bartecka; Natalia Kuczka; Agnieszka Bielaszka; Marzena Tudrej; Oskar Kowalski; Marek Kardas (Foods)
Background/Objectives: The development of culinary tourism offers not only unique culinary travel experiences but also allows for the exploration of various aspects related to food. The main aim of this study was to assess the food preferences of a selected group of female consumers regarding world cuisine and to analyze the sensory quality of selected world cuisine products: ayran, rice noodles, tempeh, and chorizo. Methods: Sensory evaluation of utility characteristics, including color, aroma, texture, appearance, and taste, was conducted using a five-point scale. A custom questionnaire was used to collect data on respondents’ preferences and demographic characteristics. This study included 51 sensory panelists and 356 survey participants. Results: Among the evaluated products, rice noodles received the highest median rating (Me = 4.8), while tempeh scored the lowest (Me = 3.8). Statistical analysis revealed significant differences in sensory perceptions depending on prior product familiarity. Italian (67.5%) and Polish (65.8%) cuisines were most frequently preferred, whereas Indian cuisine (4.3%) was the least popular. Additionally, over 83% of respondents indicated they regularly patronize food establishments offering regional dishes during travel. Conclusion: This study highlights a strong preference for familiar cuisines, such as Italian and Polish, among Polish female consumers, with implications for targeted marketing strategies in the gastronomy sector. The sensory analysis provides actionable insights into product acceptance, emphasizing the importance of cultural adaptation in promoting international food products.